2013
DOI: 10.1016/j.cognition.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between language and vision: It’s momentary, abstract, and it develops

Abstract: In this paper, we present a case study that explores the nature and development of the mechanisms by which language interacts with and influences our ability to represent and retain information from one of our most important non-linguistic systems-- vision. In previous work (Dessalegn & Landau, 2008), we showed that 4 year-olds remembered conjunctions of visual features better when the visual target was accompanied by a sentence containing an asymmetric spatial predicate (e.g., the yellow is to the left of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
2
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 51 publications
4
49
2
1
Order By: Relevance
“…Nardini et al (2006) showed a transition in intrinsic reference frame selection between 4 and 5 years of age, but their “surprise trial” results suggested that verbal encoding was not driving this developmental change. These findings contrasted with research suggesting that children’s language abilities account for development changes on a range of spatial tasks (Dessalegn & Landau, 2008, 2013; Hermer-Vazquez et al, 2001; Loewenstein & Gentner, 2005; Pruden et al, 2011; Shusterman et al, 2011; Simms & Gentner, 2008). One possible explanation for this variation across tasks could be that language supports various types of spatial skills differently over development.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Nardini et al (2006) showed a transition in intrinsic reference frame selection between 4 and 5 years of age, but their “surprise trial” results suggested that verbal encoding was not driving this developmental change. These findings contrasted with research suggesting that children’s language abilities account for development changes on a range of spatial tasks (Dessalegn & Landau, 2008, 2013; Hermer-Vazquez et al, 2001; Loewenstein & Gentner, 2005; Pruden et al, 2011; Shusterman et al, 2011; Simms & Gentner, 2008). One possible explanation for this variation across tasks could be that language supports various types of spatial skills differently over development.…”
Section: Discussioncontrasting
confidence: 93%
“…One possible explanation for this variation across tasks could be that language supports various types of spatial skills differently over development. For instance, spatial recall may rely less on language than object recognition (Dessalegn & Landau, 2008, 2013) or reorientation (Hermer-Vazquez et al, 2001). Alternatively, it could be the case that effects of language were not apparent in Nardini et al’s task because their paradigm was not designed to test language specifically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations